2022
DOI: 10.1155/2022/9613721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine Low Doses with or without Midazolam in Cats: Clinical, Hemodynamic, Blood Gas Analysis, and Echocardiographic Effects

Abstract: Objectives. The aim of the study is to compare the sedative, cardiorespiratory, echocardiographic, and blood gas effects of dexmedetomidine and methadone associated or not with midazolam for restraint chemistry in cats. Methods. Eighteen healthy young cats (4.06 ± 0.48 kg) were randomly sedated with two protocols, through the intramuscular route: dexmedetomidine (5 µg.kg−1), methadone (0.3 mg. kg−1) and midazolam (0.3 mg. kg−1) (DMTM, n = 9), or dexmedetomidine (7.5 µg.kg−1) and methadone (0.3 mg. kg−1) (DMT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…This is in accordance with the literature, where it has been reported that midazolam can decrease RR in cats [26,56], probably through CNS depression and muscle relaxation [57]. Furthermore, in a study by Castro et al (2022), the administration of a dexmedetomidine-midazolammethadone combination in healthy cats resulted in marked respiratory depression, described as a reduction in RR and arterial pO 2 and an increase in arterial pCO 2 [58].…”
Section: Ph Po 2 Pco 2 and Respiratory Rate (Rr)supporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with the literature, where it has been reported that midazolam can decrease RR in cats [26,56], probably through CNS depression and muscle relaxation [57]. Furthermore, in a study by Castro et al (2022), the administration of a dexmedetomidine-midazolammethadone combination in healthy cats resulted in marked respiratory depression, described as a reduction in RR and arterial pO 2 and an increase in arterial pCO 2 [58].…”
Section: Ph Po 2 Pco 2 and Respiratory Rate (Rr)supporting
confidence: 90%
“…Similar to our study, HCT has been reported to significantly decrease after dexmedetomidine administration [82]. Additionally, Hb concentration decreased after a dexmedetomidine-methadone combination with or without midazolam in cats [21,58].…”
Section: Haematocrit and Haemoglobinsupporting
confidence: 89%